2012
DOI: 10.1371/journal.pone.0031328
|View full text |Cite
|
Sign up to set email alerts
|

β-defensin 2 as an Adjuvant Promotes Anti-Melanoma Immune Responses and Inhibits the Growth of Implanted Murine Melanoma In Vivo

Abstract: β-defensin 2 is a small antimicrobial peptide of the innate immune system and has been thought to regulate anti-tumor immunity. However, little is known on whether β-defensin 2 could modulate melanoma-specific NK and T cell responses. In this study, we first cloned the murine β-defensin 2 gene by RT-PCR and generated the β-defensin 2 stably expressing B16 cells (B16-mBD2). Subsequently, we evaluated whether vaccination with irradiated B16-mBD2 could modulate the growth of implanted B16 cells and determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 19 publications
1
28
0
1
Order By: Relevance
“…This effect is probably due to the more efficient maturation and activation of immature dendritic cells (iDC) mediated by mBD-2 in a TLR4-dependent manner [20]. These results are also consistent with published reports in cancer models, in which DNA vaccines expressing β-defensin-2 increased the immune response specifically against strong or poorly immunogenic neoplastic antigens in different cancer types [23,24,37]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This effect is probably due to the more efficient maturation and activation of immature dendritic cells (iDC) mediated by mBD-2 in a TLR4-dependent manner [20]. These results are also consistent with published reports in cancer models, in which DNA vaccines expressing β-defensin-2 increased the immune response specifically against strong or poorly immunogenic neoplastic antigens in different cancer types [23,24,37]. …”
Section: Discussionsupporting
confidence: 88%
“…This is the specific case of β-defensin-2, an antimicrobial peptide that induces dendritic cell maturation in a Toll-like (TLR) receptor 4-dependent manner [1921]. Interestingly, genetic construct coding sequences of β-defensin-2 generate a polarized and antigen-specific Th1 immune response [2224]. This is important because multiple reports indicate that a Th1/CD8+ cytotoxic cellular immune response is essential for Mtb growth control [25].…”
Section: Introductionmentioning
confidence: 99%
“…A DNA vaccine containing the Mbd2 gene linked to the human immunodeficiency virus (HIV) envelope (ENV) gene delivered into the skin by a gene gun induced enhanced ENV-specific mucosal as well as systemic immune responses in mice (Biragyn et al, 2002a). Furthermore, several recent studies have demonstrated the potential of Mbd2 to augment antitumor immune responses and mediate tumor regression when fused with tumor antigens or over expressed in irradiated tumor cells (Lapteva et al, 2009; Mei et al, 2012; Park et al, 2011). Consistent with earlier findings, mice co-immunized with HAd-HA-NP+HAd-Mbd2 had significantly higher levels of both HA-518- and NP-147-epitope–specific CD8+T cells in the spleen and regional lymph nodes compared with those vaccinated with HAd-HA-NP alone.…”
Section: Discussionmentioning
confidence: 99%
“…Some potential strategies may include optimizing the dose of the immunostimulant vector and the vaccine vector, and optimizing the timing of immunostimulation. Moreover, defensins (both alpha and beta) have been tested extensively as immunostimulants in pre-clinical studies, and there have been no reports of any adverse effects (Lapteva et al, 2009; Mei et al, 2012; Park et al, 2011; Yang et al, 2004). It would be important to monitor the effect of immunstimulation with Mbd2 on the induction of immune responses following vaccination with an inactivated influenza vaccine.…”
Section: Discussionmentioning
confidence: 99%